DAMPAK E-COMMERCE TERHADAP PERILAKU KONSUMSI MAKANAN OLEH MAHASISWA DI YOGYAKARTA - Khusnul Fatimah; Tri Endar Suswatiningsih; Cristina Wahyu Ary Dewi (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2023)
The Impact Of E-commerce On Food Consumption Behavior By Students In Yogyakarta. Modernization in the economic field gave rise to an online selling system known as e-commerce. The emergence of e-commerce in Yogyakarta, such as shopee, grab, and gojek, has made students often use e-commerce to order food, so it needs to be studied further to determine the impact of e-commerce. This study aims to find out the e-commerce used by students, find out the variety of food purchased by students, and find out the impact of e-commerce on food consumption behavior by students. This research was conducted using a descriptive method with a qualitative-quantitative approach and the location of the research was determined using a case study at Instiper Yogyakarta. Sampling used accidental sampling criteria with solvin formula so that 97 students were obtained. The data were analyzed using t-test. The research results obtained by the e-commerce used by students at Instiper Yogyakarta are shopee (70.1%), grab (15.5%), and gojek (14.4%). Food ordered through e-commerce by students at were staples (14.4%), main meals (38.1%), desserts (30.9%), and snacks (16.5%). The positive impact of using e-commerce makes it easier to meet needs, time efficient, and energy efficient and the negative impact of e-commerce is an increase in spending, an increase in food purchases, and the emergence of consumptive behavior. Based on the results of the t test, spending after using e-commerce is greater than spending before using e-commerce.